Knowledge level and incidence of complications in diabetic patients - Krzyżanowska, Ewa; Indycka, Ewelina; Łuczyk, Robert Jan; Łuczyk, Marta; Sawicka, Katarzyna; Wawryniuk, Agnieszka; Daniluk, Jadwiga (Journal of Education, Health and Sport, 2017)
Admission. Diabetes is a civilization disease and is an important issue of modern medicine. There is an annual increase in the incidence of this disease. Type 1 diabetes affects 3-10% of all cases worldwide, while type 2 diabetes accounts for 85% of all cases. In Poland, 12-15% of people are diagnosed with type 2 diabetes. [3] Material and method. The study involved 100 patients with diagnosed type 1 and type 2 diabetes. The study was conducted in Lublin: Military Hospital, Department of Internal Diseases, SPSK 4 in the Department of Endocrinology and in the SPSK 4 Polyclinic in the Diabetological Clinic. The study was conducted from February to April 2016. Results. Most of the respondents had average knowledge about their illness. Only 18% of patients had a high level of knowledge about diabetes and 30% of low knowledge. Complications of diabetes have been more frequently seen in patients with type 2 diabetes than type 1. Conclusions. A large number of complications were diagnosed in 19% of patients, with few complications in 31% of patients. In the group of women surveyed in the city and with higher education, complications were also more frequent than in men and patients living in rural areas and those with vocational or secondary education.